2005
DOI: 10.1080/17402520500116624
|View full text |Cite
|
Sign up to set email alerts
|

PAH‐ and PCB‐induced Alterations of Protein Tyrosine Kinase and Cytokine Gene Transcription in Harbor Seal (Phoca Vitulina) PBMC

Abstract: Mechanisms underlying in vitro immunomodulatory effects of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were investigated in harbor seal peripheral leukocytes, via real-time PCR. We examined the relative genetic expression of the protein tyrosine kinases (PTKs) Fyn and Itk, which play a critical role in T cell activation, and IL-2, a cytokine of central importance in initiating adaptive immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…However, large inter-individual variability has previously been observed and cytokine expression in seal PBMCs has been found to vary widely, depending also on the duration of MeHg exposure [ 48 ]. A decrease in PBMC IL-2 expression has also been documented in harbour seals following in vitro exposure to PHA and PCB [ 37 ], raising the possibility of additive effects of MeHg and other organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…However, large inter-individual variability has previously been observed and cytokine expression in seal PBMCs has been found to vary widely, depending also on the duration of MeHg exposure [ 48 ]. A decrease in PBMC IL-2 expression has also been documented in harbour seals following in vitro exposure to PHA and PCB [ 37 ], raising the possibility of additive effects of MeHg and other organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Data indicated that early exposures to environmental toxicants could directly impact the development and function of children's immunity. Many populations in polluted areas (such as Europe and North America) may be at risk of immunotoxicity, which could then manifest as diminished host resistance and increased incidence and severity of infectious diseases (Ross et al, 2004;Neale et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous marine mammal studies have identified pinniped immune responses against PhV-1 using enzyme-linked immunosorbent (ELISA), but this offers minimal information about the disease (Harder et al, 1998). Marine mammal studies have applied targeted gene expression techniques using RT-qPCR to examine immune and endocrine responses to immunotoxins and physiological changes (Neale et al, 2005; Hammond, 2005; Tabuchi et al, 2006). However, ELISA and RT-qPCR target a limited number of host gene expressions; thus they do not represent the global host response.…”
Section: Introductionmentioning
confidence: 99%